Upaya Meningkatkan Kemampuan Motorik Kasar Anak Usia Dini Melalui Permainan Berlari dengan Rintangan di RA Uswatun Hasanah - Siti Muliyah (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to improve the gross motor skills of early childhood children through the implementation of an obstacle running game at RA Uswatun Hasanah, North Labuhanbatu. The study was motivated by the children's low gross motor skill levels, characterized by a lack of movement coordination, balance, agility, and confidence in performing physical activities. It employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, comprising the stages of planning, action implementation, observation, and reflection. The subjects were 15 children from Group B, consisting of 8 boys and 7 girls. The study was conducted over two cycles, with each cycle consisting of two sessions. Data collection techniques included observation, documentation, and field notes, while data analysis was performed using both quantitative and qualitative descriptive methods. The results indicate that the obstacle running game successfully improved the children's gross motor skills incrementally. In the pre-cycle stage, the percentage of children achieving the "Developing as Expected" (BSH) and "Developing Very Well" (BSB) categories was 33.33%. Following the intervention in Cycle I, the achievement rate rose to 66.67%, and further increased to 86.67% in Cycle II, thereby surpassing the established success indicator namely, that at least 80% of the children reach the BSH and BSB categories. Beyond enhancing running ability, balance, coordination, and agility, the obstacle running game also fostered courage, self-confidence, and active participation in the learning process. Consequently, the obstacle running game serves as an effective alternative teaching strategy to optimize gross motor development among early childhood children in Raudhatul Athfal settings.